Acute Surgical Repair of Complete, Nonavulsion Proximal Semimembranosus Injuries in Professional Athletes - Ayuob, A.; Kayani, B.; Haddad, F. S. (The American Journal of Sports Medicine, 2020)
Background: Nonoperative management of proximal semimembranosus injuries is associated with prolonged periods of convalescence and high risk of recurrence. To our knowledge, the outcomes of acute surgical repair for complete, nonavulsion proximal semimembranosus injuries have not been previously reported.